2018
DOI: 10.1186/s13041-018-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin type III domain-containing protein 5 interacts with APP and decreases amyloid β production in Alzheimer’s disease

Abstract: The deposition of Amyloid-beta peptides (Aβ) is detected at an earlier stage in Alzheimer’s disease (AD) pathology. Thus, the approach toward Aβ metabolism is considered to play a critical role in the onset and progression of AD. Mounting evidence suggests that lifestyle-related diseases are closely associated with AD, and exercise is especially linked to the prevention and the delayed progression of AD. We previously showed that exercise is more effective than diet control against Aβ pathology and cognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 61 publications
1
27
0
2
Order By: Relevance
“…A recent in vitro study, by means of biochemical and in silico simulation assay, showed the possible involvement of FNDC5/irisin in the mechanisms of Aβ generation [ 82 ]. In particular, the authors showed that APP/FNDC5 interaction, occurring by the binding of FNDC5 to a specific domain between β- and α-secretase cleavage sites of APP, could reduce Aβ formation, leading to a decreased secretion of both Aβ40 and Aβ42 peptides in the culture media.…”
Section: Irisin and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vitro study, by means of biochemical and in silico simulation assay, showed the possible involvement of FNDC5/irisin in the mechanisms of Aβ generation [ 82 ]. In particular, the authors showed that APP/FNDC5 interaction, occurring by the binding of FNDC5 to a specific domain between β- and α-secretase cleavage sites of APP, could reduce Aβ formation, leading to a decreased secretion of both Aβ40 and Aβ42 peptides in the culture media.…”
Section: Irisin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…This could imply the involvement of FNDC5 in the prevention of AD, acting in the initial phases of the disease development when Aβ accumulation begins and before the onset of dementia. Indeed, when AD is in the clinical stage, Aβ and tau accumulations have already induced extensive neuronal damage in multiple areas of the brain and could be too late for the possible FNDC5 role as of any other compound in AD treatment [ 82 ]. In vivo studies performed in animal models and in humans by Lourenco et al [ 10 , 30 ] demonstrated that irisin levels were reduced in the cerebrospinal fluid (CSF) of AD mice and patients.…”
Section: Irisin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Boosting of brain irisin by intracerebroventricular infusion rescues memory impairment and provides protection against synaptic plasticity in AD mice (Lourenco et al, 2019). Another group showed that irisin binds with amyloid precursor protein at the N-terminal and that overexpression of FNDC5 in cells significantly decreased the secretion of amyloid-β protein into the media in vitro (Noda et al, 2018). In addition, pharmacological, but not physiological, concentrations of irisin (50-100 nM) increase the proliferation of a mouse hippocampal cell line, H19-7 HN, without influencing markers of neurite outgrowth or synaptogenesis in vitro.…”
Section: Irisin Biogenesis and Biological Aspectsmentioning
confidence: 99%
“…One recent study has reported the interaction between FNDC5 and APP, and resultant decreases in Aβ formation. According to the study, although FNDC5 has no effect on full APP length, it decreases C-terminal fragment C99 of APP [76]. Since this fragment has Aβ formation-suppressing characteristic, FNDC5 expression seems to diminish Aβ production [76].…”
Section: Irisin Precursor Fndc5 and Its Upstream Pgc-1α Regulates mentioning
confidence: 99%
“…According to the study, although FNDC5 has no effect on full APP length, it decreases C-terminal fragment C99 of APP [76]. Since this fragment has Aβ formation-suppressing characteristic, FNDC5 expression seems to diminish Aβ production [76]. In this regards, both the irisin precursor, FNDC5, and its upstream factor, PGC-1α, are involved in the regulation of AD pathogenesis.…”
Section: Irisin Precursor Fndc5 and Its Upstream Pgc-1α Regulates mentioning
confidence: 99%